Male or Female, who is the highest? Life Optimism in Cardiovascular Disease Patients - Putra, Rahman Pranovri; Ramadhanti, Auliya; Puhka, Prakash; Annemari, Barreiro (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
This study aims to analyze optimism in coronary heart patients and analyze the optimism of coronary heart patients based on gender differences. This type of research is survey research with a quantitative approach. The population in this study were coronary heart disease patients who had been clinically diagnosed by a doctor and were undergoing outpatient care at RSUD Arifin Achmad Pekanbaru, with a total of 213 people, and the number of samples in this study was 139 people. Data analysis technique used in this research is descriptive statistical analysis and inferential data analysis using t-test. The results showed that there were differences in optimism from the gender of coronary heart patients. So that these findings are useful for the development of the science of positive psychology in the context of coronary heart patients.